Farmers’ Cultural Flexibility in Food Estate Development Corporate Based in Central Kalimantan - Sidik Rahman Usop (The Innovation of Social Studies Journal, 2023)
Food Estate development based on Corporate places farmers as subjects who should be able to dynamically develop themselves as advanced farmers, independent farmers, and modern farmers. These development efforts require intensive social interaction to take advantage of cultural flexibility in adapting and transforming, resulting in innovations and development towards a modern farming society. Through qualitative descriptive methods, in-depth interviews were conducted to explain the dynamics of farmers' lives in fulfilling the demands of life and responding to various challenges as part of the social realities of life that must be faced. The study results show that the farming activities in Belanti Siam Village, Pulang Pisau Regency, and Dadahup Village can gradually develop into modern farmers. With the support of stakeholders, the food estate development area can be developed as a strategic economic area to support Central Kalimantan as a supporting area for the National Capital City (IKN) Nusantara.